Pengembangan Kurikulum PAI Berbasis Multikultural - Syaiful Anwar; Nanang Budianto; Ahmad Salim Ulul Albab; Muhammad Tis Asuh Sobirin (4, 2026)
Indonesia is a country with a rich diversity of cultures, ethnicities, religions, languages, and traditions. This condition is both a strength and a challenge in the life of the nation and state. In this context, Islamic Religious Education (PAI) plays a strategic role as a means of character building for students who not only have a strong religious understanding but also are able to appreciate diversity as part of social reality. This paper aims to describe the concept of developing a multicultural-based Islamic Religious Education curriculum, explain the development procedures, and identify approaches that can be used to integrate multicultural values ​​into PAI learning materials. This study uses a library research method with a qualitative descriptive approach through analysis of various literature, scientific articles, books, and documents relevant to curriculum development and multicultural education. The results show that the development of a multicultural-based PAI curriculum is an effort to integrate the values ​​of Islamic teachings with the principles of cultural and social diversity. This curriculum is aimed at forming students who are tolerant, democratic, inclusive, have open personalities, and possess noble morals. Curriculum development is carried out through planning, implementation, and evaluation stages, systematically structured according to student needs and the characteristics of a pluralistic society. During the planning stage, learning objectives, materials, methods, and evaluation are designed with multicultural values ​​in mind. The implementation stage is carried out through learning activities that encourage dialogue, cooperation, and respect for differences. Furthermore, the evaluation stage is used to assess the effectiveness of curriculum implementation and student competency achievement in knowledge, attitudes, and behavior. Abstrak Indonesia merupakan negara yang memiliki keragaman budaya, suku, agama, bahasa, dan tradisi yang sangat kaya. Kondisi tersebut menjadi kekuatan sekaligus tantangan dalam kehidupan berbangsa dan bernegara. Dalam konteks ini, Pendidikan Agama Islam (PAI) memiliki peran strategis sebagai sarana pembentukan karakter peserta didik yang tidak hanya memiliki pemahaman keagamaan yang kuat, tetapi juga mampu menghargai keberagaman sebagai bagian dari realitas sosial. Tulisan ini bertujuan untuk mendeskripsikan konsep pengembangan kurikulum Pendidikan Agama Islam berbasis multikultural, menjelaskan prosedur pengembangannya, serta mengidentifikasi pendekatan yang dapat digunakan untuk mengintegrasikan nilai-nilai multikultural ke dalam materi pembelajaran PAI. Penelitian ini menggunakan metode studi kepustakaan (library research) dengan pendekatan deskriptif kualitatif melalui analisis berbagai literatur, artikel ilmiah, buku, dan dokumen yang relevan dengan pengembangan kurikulum serta pendidikan multikultural. Hasil penelitian menunjukkan bahwa pengembangan kurikulum PAI berbasis multikultural merupakan upaya mengintegrasikan nilai-nilai ajaran Islam dengan prinsip-prinsip keberagaman budaya dan sosial. Kurikulum ini diarahkan untuk membentuk peserta didik yang toleran, demokratis, inklusif, berkepribadian terbuka, serta memiliki akhlak mulia. Pengembangan kurikulum dilakukan melalui tahapan perencanaan, pelaksanaan, dan evaluasi yang disusun secara sistematis sesuai dengan kebutuhan peserta didik dan karakteristik masyarakat yang plural. Pada tahap perencanaan, tujuan, materi, metode, dan evaluasi pembelajaran dirancang dengan mempertimbangkan nilai-nilai multikultural. Tahap implementasi dilakukan melalui kegiatan pembelajaran yang mendorong dialog, kerja sama, dan penghargaan terhadap perbedaan. Selanjutnya, tahap evaluasi digunakan untuk menilai efektivitas penerapan kurikulum serta pencapaian kompetensi peserta didik dalam aspek pengetahuan, sikap, dan perilaku.